The state of the law's discourse in a utopian ideology - Syarifuddin Syarifuddin (Indonesia Prime, 2018)
The writing of this not just the pale of law as an event, but instead in the pale of ocherans their idealism. Conclusion This paper, Indonesia's constitutional amendment has already done four times (1999-2002), meaning the ideal act previously found, the reform agenda implements nations ' repair responsibility in law, but to shock shocks Nationality remains volatile, ranging from political, economic and social shocks. Case law spreads like a culture that should be inherited, such as inheriting the saying that goes back a standing teacher who ran the pupils. If so, the rule of law is still limited to only the utopia of Indonesia